2007
DOI: 10.1073/pnas.0701204104
|View full text |Cite
|
Sign up to set email alerts
|

Normal mode refinement of anisotropic thermal parameters for a supramolecular complex at 3.42-Å crystallographic resolution

Abstract: Here we report a normal-mode-based protocol for modeling anisotropic thermal motions of proteins in x-ray crystallographic refinement. The foundation for this protocol is a recently developed elastic normal mode analysis that produces much more accurate eigenvectors without the tip effect. The effectiveness of the procedure is demonstrated on the refinement of a 3.42-Å structure of formiminotransferase cyclodeaminase, a 0.5-MDa homooctameric enzyme. Using an order of magnitude fewer adjustable thermal paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 42 publications
0
52
0
Order By: Relevance
“…To start, several parameters for normal-mode-based refinement, including the number of low-frequency modes and the value of stiffness, were optimized by running parallel refinements (14)(15)(16)(17). We found that 75 modes with stiffness of 30 yielded the lowest R factors.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To start, several parameters for normal-mode-based refinement, including the number of low-frequency modes and the value of stiffness, were optimized by running parallel refinements (14)(15)(16)(17). We found that 75 modes with stiffness of 30 yielded the lowest R factors.…”
Section: Resultsmentioning
confidence: 99%
“…To eliminate the slight differences in structural statistics because of the use of different structural refinement programs or different versions of them, we generally reminimize the structural models from PDB (14)(15)(16)(17). In this study, the Kv1.2 structure (PDB ID code 2A79) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations